Chiloé The Ethnobiology of an Island Culture (Ethnobiology,, 2018)
This volume focuses on the ethnobiology of southern Chile's Archipelago of Chiloé. Chiloé presents a unique perspective on the intersection of society and biology owing to its vast natural resources, historic culture of cooperation, geographic isolation, and external resource exploitation. Contributions to this volume cover knowledge bases in both marine and terrestrial systems, and how specific local knowledge types contributed to a variety of strategies, including subsistence, social-ecological resilience, resource conservation, cultural heritage preservation, economic systems, and mitigating uncertainty. This book addresses the specificities of human-environment interaction on a resource-rich island, and how historic knowledge and practices can help configure adaptation to a changing social-ecological landscape.